1954
DOI: 10.1172/jci103031
|View full text |Cite
|
Sign up to set email alerts
|

17-Hydroxycorticosteroid Metabolism in Liver Disease1

Abstract: Considerable evidence has been accumulated to indicate that the liver is concerned in the metabolism of steroids (1). The development of methods for the measurement of 17-hydroxycorticosteroids in the plasma (2) and in the urine (3) has enabled us to study the role of the liver in the handling of 17-hydroxycorticosterone (hydrocortisone) and related compounds. This communication will consider the plasma levels and the urinary excretion of the 17-hydroxycorticoids in patients with liver disease as compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

1956
1956
1961
1961

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…In patients with liver disease, cortisone disappeared from the plasma at the normal rate, whereas hydrocortisone has been shown to be metabolized at a much slower rate (1,7). In patients with liver disease, cortisone was metabolized at the same rapid rate as the biologically inactive dihydro and tetrahydro metabolites of cortisone and hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with liver disease, cortisone disappeared from the plasma at the normal rate, whereas hydrocortisone has been shown to be metabolized at a much slower rate (1,7). In patients with liver disease, cortisone was metabolized at the same rapid rate as the biologically inactive dihydro and tetrahydro metabolites of cortisone and hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahydrocortisone made up the major portion of the metabolites reacting with phenylhydrazine, and tetrahydrocortisone and tetrahydrohydrocortisone accounted for 93 per cent of all the phenylhydrazine-reactive glucuronide conjugates. 7 After prior hydrolysis of the conjugated prod- 7 The following unpublished data may be pertinent to the findings that following intravenous administration of cortisone, the urinary concentration of tetrahydrocortisone glucuronide greatly exceeds the concentration of tetrahydrohydrocortisone glucuronide: Following intravenous infusion of tetrahydrocortisone, seven per cent was recovered in the urine as tetrahydrohydrocortisone, and 40 per cent as tetrahydrocortisone after glucuronidase hydrolysis. Twenty per cent of infused tetrahydrohydrocortisone was recovered in the urine as tetrahydrocortisone, and 30 per cent as tetrahydrohydrocortisone after glucuronidase hydrolysis Thus, the presence of the a, fI unsaturated 3-keto group in ring A seems to direct the enzymatic reduction of cortisone --hydrocortisone, whereas the saturated ring A seems to favor oxidation of the lipgroup (tethydrohydrocortisone -) tetrahydrocortisone).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged stress A quantitative study of the urinary metabolites from a patient severely ill for several months is shown in Table IV 14 . t The absence of detectable quantities of allo-THF is not an artifact of the paper chromatography.…”
Section: -18 Altered Ratio Op Urinary Cortisol Metabolitesmentioning
confidence: 99%
“…Together with urinary procedures (5,6) these techniques have been employed to determine the secretion of cortisol by the adrenal in normal and pathological conditions (7)(8)(9) and to evaluate the factors involved in the "removal" of cortisol from the plasma in surgery (10)(11)(12)(13) and liver disease (14)(15)(16).…”
mentioning
confidence: 99%
“…6 The same authors believe that the defect in degradation of corticoids manifested by all these types of patients lies not in failure of conjugation but is due to a block in the normal mechanism which transforms free hydrocortisone to the tetrahydroderivatives. In a few instances, hypothyroid CHART II.…”
Section: Discussionmentioning
confidence: 99%